Os católicos oPTaram?: os "setores católicos" e o Partido dos Trabalhadores (PT) na grande São Paulo (1978-1982) - Machado, Adriano Henriques (2010)
This paper discusses the relations between the various sectors Catholics in thebig region of São Paulo with the Workers s Party (PT) during the period between 1978 and 1982, from the perspectives of social history, ie, their tensions, disputes, approaches, rejections and points of identification and convergence. Inside the juncture of the various movements that have emerged over the years 1970 and later articulated the creation of PT, discusses the relations between the various Catholic groups such as: Pastoral Workers (PO), Basic Ecclesial Communities (BEC), Commissions Justice and Peace, the hierarchy itself, among others, with popular movements and labor-union movements. Moreover, examines how the hierarchy, the various groups and Catholics were related and positioned himself in the presence to political openness, reorganizing party and the elections of 1982, ie, since the joints seeking to create a Popular Party (PP), passing through the creation of the PT, it s consolidation and the involvement of party elections in 1982